Peningkatan Literasi Bahasa Inggris Melalui Gamifikasi Board Game Dalam Pembelajaran Berdiferensiasi di Kelas 6 SD Negeri Pondok 02 (Lembaga Pengembangan Kinerja Dosen, 2025)
Gamification is an instructional approach that incorporates game elements to enhance student engagement and motivation in the classroom. This classroom action research was conducted with sixth-grade elementary school students by integrating gamification techniques into the learning process. Various game-based components such as point systems, levels, challenges, and rewards were applied throughout the instructional activities. During the study, data were collected on student participation, academic achievement, and responses to the implementation of gamification. The findings indicate that gamification strategies significantly improved student involvement in the learning process. Students demonstrated greater enthusiasm and active participation during gamified lessons. Moreover, improvements in academic performance were observed among students engaged in gamification-based learning. However, further research is needed to explore in more depth the factors that influence the effectiveness of gamification across different subject areas.